Petit Dictionnaire des Artistes Modernes : Peintres - Photographes - Sculpteurs. - Le Thorel-Daviot, Pascale (Paris : Larousse - Bordas, 1999)
Abbott, Berenice ; Adams, Ansel ; Albers, Josef ; Albright, Ivan Le Lorraine ; de Almada Negreiros, José ; Altman, Nathan ; Amiet, Cuno ; Archipenko, Aleksandr ; Arp, Hans (Jean) ; Artaud, Antonin ; Atget, Eugène ; Auberjonois, René ; Ault, George ; Avery, Milton ; Baader, Johannes ; Bailly, Alice ; Bakst, Leon ; Balla, Giacomo ; Baranoff-Rossiné, Vladimir ; Barlach, Ernst ; Bauchant, André ; Baumeister, Willi ; Beckmann, Max ; Bell, Vanessa ; Belling, Rudolf ; Bellmer, Hans ; Bellows, George ; Benois, Alexandre ; Benton, Thomas Hart ; Beothy, Etienne ; van den Berghe, Frits ; Berlewi, Henryk ; Bissier, Julius ; Blanchard, Maria ; Blanche, Jacques-Emile ; Blossfeldt, Karl ; Blumenfeld, Erwin ; Boccioni, Umberto ; Boeckl, Herbert ; Bomberg, David ; Bombois, Camille ; Bonnard, Pierre ; Bortnyik, Sándor ; Bourdelle, Antoine ; Bourliouk, David & Vladimir ; Bragaglia, Anton Giulio ; Brancusi, Constantin ; Braque, Georges ; Brassaï ; Brauner, Victor ; Brooks, Romaine ; Brusselmans, Jean ; Burchfield, Charles ; Burra, Edward ; Cahn, Marcelle ; Calder, Alexander ; Camoin, Charles ; Campendonk, Heinrich ; Campigli, Massimo ; Capek, Josef ; Carlsund, Otto Gustav ; Carrà, Carlo ; Casorati, Felice ; Cavalcanti, Emiliano di ; Chabaud, Auguste ; Chagall, Marc ; Charchoune, Serge ; Chauvin, Jean-Gabriel ; De Chirico, Giorgio ; Claudel, Camille ; Cocteau, Jean ; Csáky, József ; Cunningham, Imogen ; Dali, Salvador ; Davis, Stuart ; Delaunay, Robert ; Delaunay, Sonia ; Delvaux, Paul ; Demuth, Charles ; Depero, Fortunato ; Derain, André ; Dix, Otto ; Dobson, Frank ; van Doesburg, Theo ; Domela, César ; Dominguez, Oscar ; van Dongen, Kees ; Douglas, Aaron ; Dove, Arthur Garfield ; Drtikol, Frantisek ; Duchamp, Marcel ; Duchamp-Villon, Raymond ; Dufresne, Charles ; Dufy, Raoul ; etc.
Bibliografie
Biografie
Frans
boek